Estimating the Direct Economic Damage of the Earthquake in Haiti - Eduardo Cavallo; Andrew Powell; Oscar Becerra (Inter-American Development Bank (IDB), 2010)
This paper uses simple regression techniques to make an initial assessment of the monetary damages caused by the January 12, 2010 earthquake that struck Haiti. Damages are estimated for a disaster with both 200,000 and 250,000 total dead and missing (i.e., the range of mortality that the earthquake is estimated to have caused) using Haitis economic and demographic data. The base estimate is US8.1bn for a death toll of 250,000, but for several reasons this may be a lower- bound estimate. An estimate of US13.9bn for the same death toll is within statistical error. While the results are subject to many caveats, the implications of such an estimate are significant. Raising such a figure will require many donorsbilateral, multilateral and private. Hence excellent coordination of funding and execution will be the key to ensuring the efficient use of funds.
Keywords: O11; O19; O54; Q54; F35; 330; Natural disasters; direct economic damages; Haiti; earthquake; reconstruction; aid and development